2017
DOI: 10.1128/mbio.00382-17
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility in the Immunoglobulin-Like Domain of the Hepatitis C Virus Glycoprotein E2

Abstract: The hepatitis C virus (HCV) glycoprotein E2 is the major target of neutralizing antibodies and is therefore highly relevant for vaccine design. Its structure features a central immunoglobulin (Ig)-like ␤-sandwich that contributes to the binding site for the cellular receptor CD81. We show that a synthetic peptide corresponding to a ␤-strand of this Ig-like domain forms an ␣-helix in complex with the anti-E2 antibody DAO5, demonstrating an inside-out flip of hydrophobic residues and a secondary structure change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 53 publications
4
31
0
Order By: Relevance
“…Our computational and bioinformatics approach, in concert with various previous observations [39,51,52], provide good evidence that conformational plasticity and intrinsic disorder are defining features of the E2 glycoprotein. We sought to further verify this using biophysical analysis.…”
Section: Saxs Analyses Of E2 Are Consistent With In Silico Experimentssupporting
confidence: 57%
See 1 more Smart Citation
“…Our computational and bioinformatics approach, in concert with various previous observations [39,51,52], provide good evidence that conformational plasticity and intrinsic disorder are defining features of the E2 glycoprotein. We sought to further verify this using biophysical analysis.…”
Section: Saxs Analyses Of E2 Are Consistent With In Silico Experimentssupporting
confidence: 57%
“…There are numerous pieces of evidence that HCV E2 exhibits high conformational plasticity [39,51,52]. For example, initial E2 crystallization attempts required the removal of HVR-1, HVR-2 and AS412, this suggests they are not conducive to ordered crystal packing and, therefore, are likely to be flexible [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…These contrasting results may be the result of greater spatial separation between E2-bound HEPC98 and HEPC74 relative to E2-bound H77.16 and HC-11. This model is plausible, since recent studies have suggested that this region of E2 is highly flexible (39,40), so NAbs with overlapping epitopes might bind to different epitope conformations or bind with different angles of approach. The structural relationship between these adjacent neutralizing epitopes certainly warrants further investigation.…”
Section: Experimental Inhibitionmentioning
confidence: 98%
“…Given recent evidence of mobility of key E2 epitopes associated targeted by neutralizing antibodies (Deng et al, 2014 ; Li et al, 2015 ; Meola et al, 2015 ; Kong et al, 2016 ; Vasiliauskaite et al, 2017 ), as noted above, stabilization of these epitopes is an intriguing option for future vaccine design efforts, particularly in light of promising recent studies in this regard for other viruses. Recent studies on engineering HIV SOSIP gp140 trimers include designing a stabilized closed protein conformation while decreasing exposure of non-neutralizing epitopes (de Taeye et al, 2015 ), as well as generation of new “hyperstable” SOSIP designs with engineered disulfide bonds that elicit improved neutralizing antibodies (Torrents de la Peña et al, 2017 ).…”
Section: Rational Design Of An Hcv Vaccinementioning
confidence: 98%
“…Over the past 5 years, a number of studies have helped to elucidate structural features of E1 and E2, as noted in recent reviews (Khan et al, 2015 ; Kong et al, 2015a ; Pierce et al, 2016a ). These have collectively shown that key epitopes targeted by broadly neutralizing antibodies on the “front layer” of E2, which corresponds to the CD81 binding face, exhibit structural heterogeneity, in particular E2 antigenic domain E (Kong et al, 2012 ; Li et al, 2015 ; Meola et al, 2015 ), as well as antigenic domains B and D (Kong et al, 2013 ; Deng et al, 2014 ; Keck et al, 2016b ; Vasiliauskaite et al, 2017 ). This has been underscored by a recent study, which combined experimental structural and biophysical characterization with simulations to characterize mobility of the CD81 binding region of E2 (Kong et al, 2016 ).…”
Section: Hcv Envelope Structure and Antibody Recognitionmentioning
confidence: 99%